Transfer of technology to developing countries by France's small and medium-sized enterprises : study - Bertin, Gilles Y.; United Nations Conference on Trade and Development. Secretariat ([Document] / United Nations, 1986)
Summary (s. vi).
Keywords: yritykset : Ranska; teknologian siirto : kehitysmaat; ulkomaankauppa : Ranska